Cover Picture: Precursor‐Directed Nucleation and Self‐Assembly Growth: From Hollow Microprisms to Nanoplatelets (ChemNanoMat 5/2017). Issue 5 (18th April 2017) - Li, Zhaojin; Hu, Tao; Peng, Zhenzhen; Hu, Minmin; Zhu, Kongjun; Wang, Xiaohui
Abstract : Achieving controlled synthesis of nanocrystals requires insight into the formation mechanism. The formation mechanism that determines the nucleation and growth for LiFePO4 nanoflakes has been visualized by using Li3 PO4 microprisms as the precursor and as a solid 'tracer'. The sluggishly dissolved precursor facilitates simultaneous heterogeneous nucleation of LiFePO4 on undissolved Li3 PO4 and homogeneous nucleation in solution. Vertically aligned nanoribbons on the Li3 PO4 surface show self‐assembly growth of primary LiFePO4 through oriented attachment. A further ripening step transfers these nanoribbons into LiFePO4 nanoplatelets. More information can be found in the Communication by X. Wang, et al. onpage 292 in Issue 5, 2017 (DOI:10.1002/cnma.201700007 ).